Constructief. - Bourgeois, Marc; Pil, Eric; Verhaegen, Dirk (Mortsel : Gemeentebestuur Mortsel, 1994)
Van den Abbeel, Jan ; Baekelmans, Guy ; Bergen, Emiel ; Bertrand, Gaston ; De Boeck, Felix ; Bruyninckx, Rob ; Cortier, Amédée ; Cuvelier, Werner ; Decock, Gilbert ; Donas, Marthe ; Van Dooren, Edmond ; Van Doorslaer, Etienne (Maur-Etienne) ; Dries, Jan ; Ganzevoort, Wybrand ; Gees, Paul ; Gentils, Vic ; Heyvaert, René ; Jespers, Floris ; Kiemeneij, Jan ; Leblanc, Walter ; Leonard, Jos ; Maes, Karel ; van den Meersch, Vincent ; Mees, Guy ; de Mey, Gaston ; Mouton, Jef ; Peeters, Jozef ; Peire, Luc ; Ramon, Renaat ; Rubens, Albert ; De Sauter, Willy ; Servranckx, Victor ; Van Severen, Dan ; Van Sumere, Hilde ; Swimberghe, Gilbert ; De Troyer, Prosper ; Vandenbranden, Guy ; Vantongerloo, Georges ; Verhaegen, Dirk ; Vermeulen, Noël ; Verstockt, Mark ; Vuylsteke, Jaak
Nederlands
Constructief, Gemeentehuis Mortsel, 22 october tot 7 november 1994
boek